Chromosome number variation in two antipodean floras - Peruzzi, Lorenzo (Oxford University Press, 2011)
BACKGROUND AND AIMS: We compared chromosome number (CN) variation in the nearly antipodean Italian and New Zealand floras to verify (i) whether patterns of variation reflect their similar latitudinal ranges or their different biogeographic/taxonomic contexts, (ii) if any differences are equally distributed across major taxa/lineages and (iii) if the frequency, number and taxonomic distribution of B-chromosomes differ between the two countries. METHODOLOGY: We compared two datasets comprising 3426 (Italy) and 2525 (New Zealand) distinct cytotypes. We also compared a subset based on taxonomic orders and superimposed them onto a phylogeny of vascular plants. We used standard statistics, histograms, and either analysis of variance or Kruskal–Wallis tests to analyse the data. PRINCIPAL RESULTS: Mean CN of the vascular New Zealand flora is about twice that of Italy. For most orders, mean CN values for New Zealand are higher than those of the Italian flora and the differences are statistically significant. Further differences in CN variation among the orders and main clades that we studied, irrespective of geographical distinctions, are revealed. No correlation was found between chromosome and B-chromosome number. CONCLUSIONS: Mean CN of the whole New Zealand dataset is about twice that of the Italian flora. This suggests that extensive polyploidization played a major role in the evolution of the New Zealand vascular flora that is characterized by a rate of high endemism. Our results show that the hypothesis of a polyploid increase proportional to distance from the Equator cannot be applied to territories with the same latitudinal ranges but placed in different hemispheres. We suggest that bioclimatic gradients, rather than or in addition to latitudinal gradients, might account for a polyploidy increase. Our data also suggest that any adaptive role of B-chromosomes at geographic scale may be sought in their frequency rather than in their number.